Daily PHYSICAL activity (DPA) IS markedly REduced in maintenance hemodialysis (MHD) patients - JC Kim; BB Shapiro; M Zhang; J Porszasz; U Feroze; R Upreti; Y Li; K Kalantar-Zadeh; JD Kopple (The Korean Society of Nephrology, 2012)
patients are considered to be physically less activity than normal, but there are only few studies on this question. We measured DPA over 7 days, with the new Actigraph GT3X+ Activity Monitor®, on 63 patients receiving MHD 3Xwk for ≥6 months and 36 matched normals. Patients were 52±14SD years, 30% female; 35% diabetic; dialysis vintage, 61±47 mos. Normals were 49±12 years, 42% female, with similar racial/ethnic mix. The average daily vector magnitude for DPA, calculated as the square root of the sum of the squares of the three dimensional axes, was much lower in MHD, 398,868 counts (counts include HD days), vs. Normals (651,685 counts, P<0.001). In MHD vs Normals, % time in sleep or marked physical inactivity was 81% vs 73% (P<0.001); % time in ≥moderate activity, 4.0% vs 7.0% (P<0.001). In MHD, there was a trend toward increasing physical activity as patients progressed from the HD day to one day and then two days post-HD (Two days post-HD vs. HD day, p=0.015). This trend might be due to reduced activity in the HD unit, increased physical activity on weekends, or exhaustion from HD. Thus, compared to matched normal adults, MHD patients have markedly reduced DPA. Since study subjects had to be willing and able to complete physical performance tests, the most debilitated MHD patients were not recruited to the study. Hence, decreased DPA in MHD patients might be even greater than observed. Hemodialysis (HD) Day 1 day Post-HD 2 days Post-HD Normal Controls Vector Magnitude Daily Average (Counts/Day ± SD) 347122± 135299 389077±168033 417870±174145 651685±58283† P-Value relative to day of HD (2-tailed) 0.138 0.015* <0.001